Development of Electrical Car Learning Media as A Future Alternative Car - Supari Muslim; Tri Wrahatnolo; Sri Handayani; Erina Rahmadyanti; Nita Kusumawati; Achmad Imam Agung (JETL (Journal of Education, Teaching and Learning), 2020)
This research aims to: (1) develop Electric Car Learning Media through research and development (R&D) ADDIE Model (Analysis, Design, Development, Implementation, and Evaluation); (2) knowing the level of feasibility of learning media for electric cars (LMEC) in a learning perspective; and (3) to determine the effectiveness of LMEC in the learning process. The study found that: (1) based on the validator's assessment, that the LMEC that had been developed was very suitable for use in learning Electric Cars; (2) based on student assessment, that LMEC is very suitable for use in learning Electric Cars in the Department of Electrical Engineering, State University of Surabaya; and (3) LMEC is very effective, proven as many as 24 (77.41%) of students get a score of learning outcomes in the range 71-100, with good and excellent categories.